Nematodes from the caecum and colon of Pogonomys (Muridae: Anisomyini) from Papua New Guinea with the descriptions of a new genus of Oxyuridae (Nematoda: Oxyurida) and a new species of Trichuridae (Nematoda: Enoplida) - Smales, L. R. (Zootaxa, 2013)
Nematodes, comprising 2 species, a new genus from the family Syphaciidae and a new species from the family Trichuridae were collected from the lower digestive tracts of 4 species of Pogonomys; P. championi, Flannery (12 individuals), P. loriae, Thomas (14 individuals), P. macrourus, (Milne Edwards) (19 individuals) and P. sylvestris, Thomas (27 individuals) from Papua, Indonesia and Papua New Guinea. Pogonomicola rugala n. gen., n. sp. differs from all other genera in the Sypaciidae in having cervical alae with numerous folds and a single weakly defined mamelon. Trichuris germani n. sp. differs from all congeners, including the cosmopolitan T. muris, the only other trichurid reported from the region, by the lengths of the spicules and vagina, the ratio of anterior to posterior body length and the number of convolutions of the testis. The genus Pogonomys, with four species from four nematode families had a relatively rich helminth fauna in the lower digestive tract compared to other ansomyins studied. The Oxyuridae, with three genera comprising 5 species was the dominant group found in the lower digestive tract of the Anisomyini, indicating the possibility that the isolation of the old endemic rodents in New Guinea has been associated with a period of coevolution between anisomyin hosts and their syphaciine parasites.